Seminar On The Use Of Social Media As Business Promotion In The Digital Economy Era For Students Of SMAN 5 Mataram As A Form Community Service - Syifa Ramadhani; Joni Rokhmat (Postgraduate Program, University of Mataram, 2025)
The rapid development of the digital economy in Indonesia opens up great opportunities for the younger generation to develop businesses through social media. However, digital literacy and marketing skills among students still need to be improved. This article describes the implementation of the seminar